Sierra Leone - Community Reintegration and Rehabilitation - Mohan, P.C. (World Bank, Washington, DC, 2012)
The objective of the project (Credit of US$25 million from the World Bank over the period 2000-2003) was to support the peace process and expedite the return of stability to Sierra Leone through the support of two initiatives - one that helped reintegrate demobilized combatants into social and economic life and the other that sought to restore basic socioeconomic infrastructure and services in the communities most affected by the war. The successful implementation of the project was also a precondition for any other Bank investment in Sierra Leone.